Intervenções de enfermagem face à ausência de rede familiar dos idosos durante a hospitalização - Miranda, Ana Beatriz Rodrigues de Sá e (2014)
Population aging is a national, European and global phenomenon, having individual and social consequences, impacting not only in the health system’s level, but also in society in General. With age, in most cases, adds a health decline, and it is necessary the intervention and hospitalization at that level. At the time of admission, there is multidisciplinary team that hosts, and the Nurses are the professionals in permanent benefit to patients But will be the Nurses awake, for whom is the family of the wearer and to integrate in care? Do they identify this fail and put into practice interventions that seal this absence? The research question of this dissertation is: in the absence of family support network at the time of hospitalization, medical service Hospital de Santa Maria 1, what are the nursing interventions carried out to address this absence? This study’s sample is the Nurses who work in internal medicine I of the Hospital of Santa Maria. For nurses is important to know the wearer the bio-psycho-social level-espitual, contributing to an individualized care and the development of a therapeutic relationship. This relationship should include the family, because she is a target of interventions and health education.